Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00266-003-0117-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Bupivacaine and Ropivacaine for Infiltration Analgesia for Bilateral Breast Surgery

Abstract: Local anesthesia infiltration has been established as a preferred method of perioperative analgesia in many cosmetic operations. In an attempt to maximize the risk-benefit ratio of local anesthesia, a study was conducted to compare efficacy of two local anaesthetic agents. Bupivacaine was compared to ropivacaine in a bilaterally symmetrical breast surgery model. A local anaesthetic solution containing either bupivacaine or ropivacaine was infiltrated into each of the breasts of 15 patients undergoing either br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…Adequately relieving acute post‐operative pain, both reduces the likelihood of developing chronic pain syndromes as well as helping reduce patients' recovery time . Also consistent with the literature, our study showed that pain scores were greatest when first measured at the 4‐h post‐operative time frame where intra‐operative analgesics were likely to have worn off. This finding is reinforced by time frame analysis, which showed the largest amounts of stronger analgesics being used in this same time frame.…”
Section: Discussionsupporting
confidence: 87%
“…Adequately relieving acute post‐operative pain, both reduces the likelihood of developing chronic pain syndromes as well as helping reduce patients' recovery time . Also consistent with the literature, our study showed that pain scores were greatest when first measured at the 4‐h post‐operative time frame where intra‐operative analgesics were likely to have worn off. This finding is reinforced by time frame analysis, which showed the largest amounts of stronger analgesics being used in this same time frame.…”
Section: Discussionsupporting
confidence: 87%
“…The results in this area are mixed with several studies showing significant pain reduction [11,12,14] while other studies did not find a reduction in pain or had mixed results [10,13,[16][17][18].…”
Section: Introductioncontrasting
confidence: 40%
“…Bupivacaine HCl is a long-acting local anesthetic commonly used for wound infiltration following breast surgery [61][62][63]. Any efficacy, however, is limited by its duration of action of approximately 12 hours [64][65][66].…”
Section: Liposome Bupivacainementioning
confidence: 99%